Recent topics of lung neuroendocrine tumors - Ichiki, Yoshinobu; Matsumiya, Hiroki; Mori, Masataka; Kanayama, Masatoshi; Nabe, Yusuke; Taira, Akihiro; Shinohara, Shinji; Goto, Hidenori; Kuwata, Taiji; Takenaka, Masaru; Oka, Soichi; Chikaishi, Yasuhiro; et al. (Journal of Thoracic Disease; Vol 11, No 8 (August 31, 2019): Journal of Thoracic Disease, 2019)
Pulmonary neuroendocrine tumors (NET), a subtype of lung cancer, comprises typical carcinoids (TCs), atypical carcinoids (ACs), large cell neuroendocrine carcinoma (LCNEC), and small cell lung carcinoma (SCLC). TCs and ACs are low-to-intermediate malignant tumors, on the other hand LCNEC and SCLC are high-grade carcinomas (1).